Long‐term outcomes and toxicities of carbon‐ion radiotherapy in malignant tumors of the sphenoid sinus - Hagiwara, Yasuhito (Head Neck, 2019)
BACKGROUND: Most of the primary sphenoid sinus tumors present with locally advanced stages with involvement of adjacent critical structures and are not amenable to radical resection. We sought to evaluate the safety and efficacy of carbon‐ion radiotherapy (C‐ion RT) for sphenoid sinus malignancies. METHODS: This is a retrospective analysis of 22 patients of primary sphenoid carcinomas treated with definitive C‐ion RT. RESULTS: Adenoid cystic carcinoma was the most common histology (15 patients, 68.2%). The median follow‐up of this cohort was 48.5 months. The actuarial local control and overall survival at 5 years were 51.0% and 62.7%, respectively. Grade 4 visual impairment and grade 4 brain necrosis were seen in six and one patient, respectively. CONCLUSION: C‐ion RT can provide a reasonably good clinical outcome in locally advanced sphenoid sinus malignancies with a marginally higher late toxicity profile because of extremely close proximity of the target volume to critical structures.